License Plate Recognition Integrated with Android and Mobile Vision - Muhammad Rizky Adinugroho; Eko Junirianto; Annafi' Franz (Politeknik Pertanian Negeri Samarinda, 2021)
License plate is an important thing on vehicle. License plate is an identity of vehicle. All of the information about type, year, tax, and owner of vehicle. The development of technology especially in digital image processing and mobile android technology. There are so many android applications that used digital image processing known as optical character recognition. The purpose of this paper is to make an android application that can recognize license plate with mobile vision library. The research method of this paper is waterfall, starts with integrating android with mobile vision library and doing test to find out the accuracy of mobile vision. Designing an application models with flowchart diagram and unified modelling language.